Prospecting competency scenarios on information as an instrument for competitive intelligence - Azevedo, Alexander Willian; Araújo, Wagner Junqueira de; Duarte, Emeide Nóbrega (InCID: Revista de Ciência da Informação e Documentação, 2017)
Competitive intelligence in the context of contemporary organizations has been presented as an important tool in the face of constantly unstable environments. However, for competitive intelligence activities to be developed with mastery, information competence (Coinfo) is presented as an approach for identifying, collecting, mapping, storing, analyzing and disseminating information that enables market analysis, decision-making and the realization of the competitive intelligence cycle. The goal of this article was developed prospective scenarios in which the attributes of information competencies are understood as a competitive differential in organizations. Using the technique of analysis of prospective scenarios, the present study works with the simulation model showed by Rojo, looking for to developed prospective scenarios of information competencies for competitive intelligence analysts. Thus, the construction of the simulated scenarios allowed us to identify conditions for organizations to prepare in advance for possible future changes, reducing their organizational uncertainties.